A porphyrin-based metallacage for enhanced photodynamic therapy. Issue 17 (12th April 2022) - Jiao, Jingjing; He, Jing; Li, Mengmeng; Yang, Jingxia; Yang, Hong; Wang, Xiaoqing; Yang, Shiping
Abstract : A porphyrin-based metallacage combined with HAase (PM@HAase-mPEG) was designed for enhanced photodynamic therapy. Abstract : In this study, we designed an effective nanoplatform to improve the photodynamic therapy (PDT) of porphyrins. Combining a porphyrin-based metallacage (PM), hyaluronidase (HAase) and DSPE-mPEG2000 together, the nanoparticle (PM@HAase-mPEG) showed enhanced PDT efficacy. The PM improved the stability of the porphyrin, avoided its aggregation and provided cavities to concentrate oxygen molecules, which was beneficial for enhancing PDT. HAase degraded HA to increase the intracellular accumulation of nanoparticles, normalized blood vessels and relieved hypoxia in tumors. PM@HAase-mPEG inhibited the growth of tumors in a 4T1 mouse model by the generated singlet oxygen with excellent PDT efficacy. This study resolved the problems of the instability of PSs, less cellular accumulation of drugs, and tumor hypoxia that limited the anti-tumor application of PDT.